Extension & Development Patterns of School Cooperatives from Students’ Point of View A Case Study of Southern Khorasan Province - E Eftekhari Gol; A Heydari; J Mohammadgholi Niya; K Rousta (تعاون و کشاورزی, 2010)
Development of students’ organizations is one of the Ministry of Education executive policies, with the purpose of encouraging students’ participation and their social and conceptual capabilities. School cooperatives as a type of these organizations face issues & problems in execution and organizing. Therefore this research has been carried out with the purpose of investigating the extension  & development patterns of school cooperatives in 2009. This research is applied, quantitative and somewhat prospective. The research’s statistical population includes students that are a member of school cooperatives board of directors that were placed into census because of limited numbers. Questionnaire and interviews were used to collect data and validity of these was approved by experts, managers and researchers. Research reliability was also measured by Cronbach Alpha coefficient which was assessed approximately 79%. The results show that it was observed no significant relationship between the respondents’ personal variables and cooperative characteristics with successfulness, unsuccessfulness and development of school cooperatives. In classification of factors affecting cooperatives success, factor analysis type R was used and it was found out that support (19.89% variance), training (14.52% variance), performance-economy (12.42% variance), society (11.96% variance), efficiency- information (10.64% variance) factors were affecting cooperatives success, a total of 69.45% variance. Factors contributing to cooperatives unsuccessfulness also comprise of program-structure (16.27% variance), supervision-law (15.19% variance), time-administrative (14.90% variance), need assessment-participation (14.57% variance) and objective-function (10% variances) factors that in sum indicates 70.96% variance of unsuccessfulness. Effective factors on cooperatives development were also classified as motivation-awareness (21.81% variance), education (14.49% variance), program-development (13.52% variance), support (12.53% variance), responsibility (10.88% variance) and peer groups (6.41% variance) factors that in sum indicates 79.68% variance of  factors contributing to cooperatives’ development.